Risk Factors of Oral Carcinoma in a Tertiary Level Hospital in Bangladesh (Journal of Monno Medical College, 2023)
Background: Cancer continues to be a major health problem despite advances in medical technology for its diagnosis and treatment. Oral cancer is the eighth most common cancer in the world. Oral cancer is a multifactorial disease- smoking, betel-nut and betel-leaf chewing habit, bad oral hygiene, and drinking alcohol are the most important factors associated with oral cancerObjectives: To identify the risk factors of oral cancer in a tertiary level hospital in Bangladesh.Methods: A total of 52 patients, aged between fifth to seventh decades, were included in this observational type of cross-sectional study. The study was conducted over the period of six months, from March to August, 2016, in the department of ENT & Head Neck surgery in Dhaka Medical College Hospital, Dhaka. Patients were randomly assigned to one of three groups by card sampling.Results: Among the 52 patients with oral cavity carcinoma, 30(57.69%) were males and 22(42.31%) females. Most patients were from rural areas (30, 57.69%), including agricultural workers 17(32.69%), daily labourers (5, 9.62%), fishermen (3, 5.77%) and others (5, 9.62%). High-risk habits were prevalent among the cases, with 24(46.14%) engaged in Pan (betel leaf) chewing and 15(28.85%) in smoking. Clinical features included ulceration, neck lump, pain, swelling, dysphagia, and bleeding. The most affected areas were buccal mucosa (19, 36.54%) and oral tongue (14, 26.92%). Histopathologically, 27(42.31%) were well-differentiated, 22(51.92%) moderately differentiated, and 3(5.77%) poorly differentiated squamous cell carcinoma. The study provides insights into the demographics and characteristics of oral cavity carcinoma patients.Conclusion: Personal habits like pan, betel-nut, tobacco chewing, ignorance, lack of proper education of oral hygiene, lack of medical facilities and poor referral system are the common factors for aggressiveness of the disease.Journal of Monno Medical College, June 2023; 9 (1): 11-14